PLANEACIÓN DE CAPACIDAD Y ANALÍTICA AUMENTADA CON ELASTICSEARCH - Gian Piero D'amico (Revista Ingeniería, Matemáticas y Ciencias de la Información)
This article presents the application of Elasticsearch as a solution for capacity planning and augmented analytics in theenterprise field, Elasticsearch is a powerful data search and analysis tool that allows organizations to manage largevolumes of information efficiently and in real time. In the context of capacity planning, Elasticsearch provides companieswith the ability to collect and analyze data in real time to forecast and adjust their resources based on demand. Thisenables more accurate and optimized planning of resources, which in turn improves operational efficiency and reducesunnecessary costs. In addition, Elasticsearch facilitates augmented analytics, which combines the power of artificialintelligence and machine learning with data visualization, enabling organizations to gain deeper and more valuableinsights from their data, identify hidden patterns and trends, and make more informed and strategic decisions.